PENGENALAN ETIKA MEDIA SOSIAL DI SMK MUHAMMADIYAH - Santoso, Bambang; Octaviano, Alvino; Sofiana, Sofa (JAMAIKA: JURNAL ABDI MASYARAKAT, 2022)
Social media is a medium for socializing with each other and is done online which allows humans to interact with each other without being limited by space and time. Nowadays almost everyone uses social media for various purposes. Some use it for sales promotions, some to improve their image, or some just as a means of communication between relatives and friends. Regardless of their needs, there must still be rules that are upheld when someone uses social media. As with other communication media, social media cannot be separated from ethics when used. Both from a psychological, sociological, and information technology perspective. In the aspect of information technology, there are things that should be considered in social media. One of them is the presence of a virus. Viruses spread by shared links, in downloaded programs, or by clicking buttons. Another thing to note is the existence of phishing or the likeness of the sender to one particular entity. For example a bank or other official institution. Then ask us to provide sensitive data. This is primarily to make a profit financially. Besides that, there are also hoaxes or fake news. Things like this need to be socialized to the public so they do not become virus spreaders, or hoax spreaders. And then, social media is a fun place to interact.